(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Thinly bedded sand-shale heterolithic are commonly found as a marginal reservoir in the Malay Basin. In the evaluation of heterolithic reservoirs, a key challenge is to determine the appropriate petrophysical properties cutoff. This study used the Modular Dynamic Tester (MDT) pressure tests to determine the appropriate petrophysical properties cutoff applicable to heterolithic intervals. Intrinsic permeability analysis and MDT mobility plots were used to determine the cutoffs for shale volume and total porosity. Subsequently, hydrocarbon pore volume thickness (with shale volume and porosity cutoff applied) was plotted against water saturation to determine the water saturation cut-off value. In this case study, the reservoir cutoffs applied are shale volume less than 60% and total porosity in excess of 12 %. The hydrocarbon pay cutoff was set at a water saturation less than 85 %.